Analysis of the Highest Altmetrics-scored Articles in Emergency Medicine Journals - Başak Bayram; Murat Cetin; Önder Limon; Brit Long; Michael Gottlieb (Western Journal of Emergency Medicine)
Introduction: Alternative metrics (altmetrics) have emerged as invaluable tools for assessing the influence of scholarly articles. In this study we aimed to evaluate correlations between Altmetric Attention Scores (AAS), and sources and actual citations in articles displaying the highest AAS within emergency medicine (EM) journals. Methods: We conducted an analysis of EM journals listed in the Science Citation Index Expanded (SCIE) using the Altmetric Explorer tool. We analyzed the journals that received the highest number of mentions, the sources of AAS, the regions most frequently mentioned, and the geographical distribution of mentions. In the subsequent stage of our analysis, we conducted an examination of the 200 top-ranked articles that had received high AAS and were published in SCIE EM journals from January 1, 2013–January 1, 2023. We sought to determine the correlations between the AAS and the citation counts of articles on Google Scholar and the Web of Science (WOS). Results: Of 40,840 research outputs evaluated, there were 510,047 shares across multiple platforms. The AAS were present for 36,719 articles (89.9%), while 10.1% had no score. In the review of the top 200 articles with the highest AAS, the median score was 382.5 (interquartile range 301.3–510.8). Of the research output evaluated, 38% were observational studies, 13% case reports, and 13% reviews/meta-analyses. The most common research topics were emergency department (ED) management and COVID-19. There was no correlation between AAS and WOS citation numbers (rs = −0.041, P = 0.563, 95% confidence interval [CI] −0.175–0.087). There was a weak correlation identified between WOS citations and mentions on X, and a moderate correlation observed for WOS citations and blog mentions (rs = 0.330, P < .001, 95% CI 0.174 to 0.458; rs2 = 0.109, and rs = 0.452, P < .001, 95% CI 0.320–0.566; and rs2 = 0.204, respectively). However, we found a strong positive correlation between WOS citations and the number of Mendeley readers (rs = 0.873, P < .001, 95% CI 0.82–0.911, rs2 = 0.762). Conclusion: While most articles in EM journals received an AAS, we found no correlation with traditional citation metrics. However, Mendeley readership numbers showed a strong positive correlation with citation counts, suggesting that academic platform engagement may better predict scholarly impact.